2019
DOI: 10.1002/trtr.1830
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia: What Reading Teachers Need to Know

Abstract: To meet students' needs and new legislation requirements, it is important that teachers understand what dyslexia is, what it is not, and how they can support their students with dyslexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Even some scholars who draw on the IDA (2018) standards have recognized the multidimensional nature of reading. For example, Johnston (2019) cited the IDA standards, arguing for a multisensory approach that “integrates visual, auditory, tactile, and kinesthetic learning elements” (p. 340). This approach “emphasizes the structure of language across the speech sound system (phonology), the writing system (orthography), the structure of sentences (syntax), the meaningful parts of words (morphology), the relationships among words (semantics), and the organization of spoken and written discourse” (p. 341; see also IDA, 2018, 2019; Pierson, n.d.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even some scholars who draw on the IDA (2018) standards have recognized the multidimensional nature of reading. For example, Johnston (2019) cited the IDA standards, arguing for a multisensory approach that “integrates visual, auditory, tactile, and kinesthetic learning elements” (p. 340). This approach “emphasizes the structure of language across the speech sound system (phonology), the writing system (orthography), the structure of sentences (syntax), the meaningful parts of words (morphology), the relationships among words (semantics), and the organization of spoken and written discourse” (p. 341; see also IDA, 2018, 2019; Pierson, n.d.).…”
Section: Discussionmentioning
confidence: 99%
“…Goodman, 1976) that have been critiqued by structured literacy advocates (Hanford, 2018, 2019, 2020; IDA, 2019; Spear‐Swerling, 2019). Furthermore a vast majority of exemplary instructional strategies advocated by Johnston (2019)—clapping syllables, manipulating letters, rhyming activities, Elkonin boxes, writing letters on multiple surfaces, and attending to spelling patterns—are typical practices in Reading Recovery lessons (Clay, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hammill and Allen (2020) examined sixteen different dyslexia definitions and identified five common elements. Much recent research holds the following criteria in common when defining dyslexia: brain-based; occurs on a spectrum; is not related to intelligence; impairs reading ability through difficulty with phonological processing, spelling, decoding, and working memory; and can be inherited in some families (IDA, 2021;Johnson, 2019;Moats & Dakin, 2017;;Wanzek & Vaughn 2020).…”
Section: Positionality Statementmentioning
confidence: 99%
“…Birsch & Carreker (2019) explain students with dyslexia must establish "alternative circuits for word recognition to compensate for disruption of circuitry normally relied on for reading" (p. 63). Successful strategies which allow this process to occur are well-documented and include direct, explicit, multi-sensory instruction in phonemic awareness and phonics (IDA, 2017;Johnson, 2019;Kearns et al, 2019;Mills, 2018;Moats & Dakin, 2017). In addition, research has shown that direct, systematic, and multisensory instruction is the basis of effective reading instruction (Al Otaiba et al, 2019;Wanzek & Vaughn, 2020).…”
Section: Biological and Neurological Basis For Dyslexiamentioning
confidence: 99%
“…Dyslexia impairs reading comprehension fluency or accuracy and can present itself as a problem in phonological awareness, phonological decoding, processing speed, written coding, short-term auditory memory, language skills, and overt oral comprehension (Bjekić, Obradović, Vučetić, & Bojović, 2014). Numerous studies have shown impairment in reading performance in dyslexic individuals (Hemati Almdarloo & Tavakoli, 2020;Johnston, 2019). On the other hand, studies have shown that in dyslexic individuals, executive functions will also be impaired (Barbosa, Rodrigues, Mello, Silva, & Bueno, 2019;MEDINA & GUIMARÃES, 2021).…”
Section: Introductionmentioning
confidence: 99%